The Lukan audience - rediscovered? - du Plessis, Isak J. (Neotestamentica, 2000)
Richard Bauckham rejects the viewpoint that the communities, which each Gospel addresses, can be reconstructed from the text. Basically he proposes that each evangelist had no particular audience in view, but envisaged as his audience any church to which his work may find its way. Bauckham's argument is briefly explained and some preliminary comments are given, before some of the support for his theory is discussed. Special attention is given to the research by Michael B Thompson on the communicability between the churches, so that the Gospels could easily and quickly have been disseminated throughout the Mediterranean world during the first centuries C.E. More support can be gleaned from the large amount of research done by Loveday Alexander on the matter of book production in New Testament times showing the relative ease of spreading the written gospel. Focus then shifts to the genre of Luke's Gospel with special attention to Luke's biographical nature. Various viewpoints are discussed, with special attention to the contribution of Richard Burridge in Bauckham's book, dealing with the use of bioi or vitae in ancient literature. Next the role of Luke as author is briefly discussed at the hand of some technical terms occurring in the prologue (Luke 1:1-4), the effect of these on the thrust and the purpose of the story and on its primary audience (Theophilus). Finally we try to offer some indications of Luke's audience in more general terms. Some seminal contributions to Luke's Gospel are briefly discussed, firstly from a historical-critical approach, as well as the attempts from a social-scientific angle. The cumulative force of these arguments is that the Gospels do not allow us to identify, beyond a high level of generality, the audiences for which they were written. The article is concluded with some suggestions for further discussion.